1959
DOI: 10.1042/bj0730530
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of serotonin and 5-hydroxyindoles during the denaturation of oxyhaemoglobin

Abstract: 1959SUMMARY 1. The reactions between chymotrypsin and the p-nitrophenyl ester of N-benzyloxycarbonyl Ltyrosine have been studied by a fast-reaction photometric method.2. It has been shown that an N-benzyloxycarbonyl-L-tyrosine-chymotrypsin compoundis formed as an intermediate in the enzymic hydrolysis of this substrate. The formation of this intermediate compound is so fast (k > 1000 sec.-') that its kinetics could not be studied.3. A comparison of the reaction parameters of the chymotrypsin-catalysed hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1964
1964
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Curiously, compound 7 was only effective against vaccinia virus. Some of the 5-alkyl-dUrd's, namely 1 (ref 2b), 2 (ref 3), 3 (ref 2b), and 4 (ref 31), have also been the subject of previous antiviral activity studies, and the MIC50 values reported here are in good agreement with those reported earlier. The 5-alkyl-dUMP's 8-14 were not examined for antiviral activity; it is assumed that their antiviral potencies are similar, if not identical, to those of the corresponding dUrd analogues, as has been directly demonstrated for 5-ethyl-dUMP,32 5-propyl-dUMP,32 5fluoro-dUMP,30 5-bromo-dUMP,30 5-iodo-dUMP30, and 5-trifluoromethyl-dUMP.30 Neutral phosphate triesters 22-25 were generally inactive against the viral strains of Table IV at the maximum concentrations tested: 22 (300 µg/mL), 23 (400 µg/mL), 24 (150 µg/mL), and 25 (200 µg/mL).…”
Section: Resultssupporting
confidence: 89%
“…Curiously, compound 7 was only effective against vaccinia virus. Some of the 5-alkyl-dUrd's, namely 1 (ref 2b), 2 (ref 3), 3 (ref 2b), and 4 (ref 31), have also been the subject of previous antiviral activity studies, and the MIC50 values reported here are in good agreement with those reported earlier. The 5-alkyl-dUMP's 8-14 were not examined for antiviral activity; it is assumed that their antiviral potencies are similar, if not identical, to those of the corresponding dUrd analogues, as has been directly demonstrated for 5-ethyl-dUMP,32 5-propyl-dUMP,32 5fluoro-dUMP,30 5-bromo-dUMP,30 5-iodo-dUMP30, and 5-trifluoromethyl-dUMP.30 Neutral phosphate triesters 22-25 were generally inactive against the viral strains of Table IV at the maximum concentrations tested: 22 (300 µg/mL), 23 (400 µg/mL), 24 (150 µg/mL), and 25 (200 µg/mL).…”
Section: Resultssupporting
confidence: 89%
“…4). We included ascorbic acid in our assays of whole-blood serotonin 2 because it prevents hemolysis from destroying serotonin by oxidation 6 , whereas Karsenty and colleagues measured serotonin in frozen heparinized blood without ascorbic acid (Fig. 1e in ref.…”
mentioning
confidence: 99%
“…Examples are the enzymatic oxidation of 5-HT by peroxidase (Napolitano et al, 1988;Methodiewa et al, 1989;Svensson, 1989) and the nonenzymatic oxidation of 5-HT by oxyhemoglobin (Blum and Ling, 1959), by ferricytochrome (Alivisatos and Williams-Ashman, 1964), or by inorganic oxidants such as copper and AgNO3 (Eriksen et al, 1960), ammonium persulfate, potassium ferricyanide, and sodium periodate (Napolitano et al, 1988). 5-HT has been also found to be readily oxidized by human serum and erythrocyte hemolysates (Blum and Ling, 1959;Martin et al, 1960), by liver and brain microsomes (Uemura et al, 1980), and by spleen homogenates (Nelson and Huggins, 1975), but the products of these oxidation processes have been only poorly identified. Wrona and Dryhurst (1988) investigated the electrochemical oxidation of 5-HT and proposed an oxidative pathway involving the formation of phenoxyl-and nitrogen-centered radicals that could either couple to give a series of oligomeric products or lose another electron to generate an unstable quinoneimine.…”
mentioning
confidence: 99%